EDUKASI ILMU WARIS DALAM UPAYA MEMBANGUN KELUARGA DAN MASYARAKAT YANG HARMONIS BAGI WARGA CISEENG, KABUPATEN BOGOR - Roni Hidayat; Karimulloh; Afrizal Tw; Aya Yahya; Raka Radityo; Muhammad Farhan; Hasby Alamsyah; Latanza Wakaramaka (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
One of the social conflicts that often occurs within families is the dispute over the distribution of inheritance. Many cases have resulted in damaged family relationships due to inheritance issues. In various regions, including Ciseeng, Bogor Regency, many people still lack understanding of the rules for inheritance distribution according to Islamic law. Therefore, the community service team from YARSI University carried out a counseling program entitled "Education on Islamic Inheritance Law as an Effort to Build Harmonious Families and Communities for the Residents of Ciseeng, Bogor Regency." This program aimed to help the people of Ciseeng Village understand inheritance law based on Islamic sharia, so that inheritance division does not become a source of family conflict. The activity was attended by 24 participants (4 women and 20 men) aged 33–70 years. The method used was participatory, involving material presentations, interactive discussions, and evaluation through pre-test and post-test using a One Group Pre-Test and Post-Test design. The materials presented included: Introduction to Islamic Inheritance Law, Analysis of Primary Heirs, and Inheritance Application Practice. The data analysis showed a statistically significant improvement (p = 0.024). The mean pre-test score was M = 5.217 and the mean post-test score was M = 5.957 out of a maximum score of 10, indicating a 7.4% increase in participants’ understanding after the educational intervention. In addition, the majority of participants gave positive feedback on the material and implementation of the activity. These results indicate that this community service program effectively improved participants’ understanding of inheritance education according to Islamic sharia. For future programs, it is recommended to extend the duration of material presentation and Q&A sessions to achieve better learning outcomes.